Solvability of boundary value problem for second order impulsive differential equations with one-dimensional p-Laplacian on whole line - Liu, Yuji (Nonlinear Analysis: Modelling and Control, 2016)
This paper is concerned with a class of boundary value problems of the impulsive differential equations with one-dimensional p-Laplacian on whole line with a nonCarathéeodory nonlinearity. Sufficient conditions to guarantee the existence of solutions are established. Some examples are given to illustrate the main results.
Keywords: second order impulsive differential equation on whole line; one-dimensional p-Laplacian; boundary value problem; solution; fixed point theorem